Hubungan self-acceptance dengan kebahagiaan siswa - Novia Ayu Widyasari; Wa Ode Lili Andriani Nasri; Sulastry Pardede (Universitas Indraprasta PGRI, 2023)
the background of this research is the instability and immaturity of self-acceptance possessed by class VII students at SMP Negeri 9 Depok which is caused by a lack of self-confidence so that they show a tendency to be passive, shy about expressing their difficulties in learning, afraid to accept criticism and feel inferior to the condition he has, which ends up causing him to find it difficult to achieve happiness in life. The method used in this research is correlational research with a quantitative approach. The research sample was 122 students. The results of this study have a Pearson correlation coefficient of 0.720 with a significance value of 0.000 (p < 0.05) which indicates that there is a strong positive correlation between self-acceptance and the happiness of class VII students at SMP Negeri 9 Depok. This indicates that the higher the level of self-acceptance, the higher the happiness level of class VII students at SMP Negeri 9 Depok. Conversely, the lower the level of self-acceptance, the lower the happiness level of class VII students at SMP Negeri 9 Depok.